2004
DOI: 10.1055/s-2004-831317
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Methoxyolivacine and Olivacine by Friedel-Crafts Reaction of Indole-2,3-dicarboxylic Anhydride with 2,4,6-Trimethoxypyridine

Abstract: 1-Benzylindole-2,3-dicarboxylic anhydride (1) was reacted with 2,4,6-trimethoxypyridine in the presence of titanium(IV) chloride to give 3-(2,4,6-trimethoxynicotinoyl)indole-2-carboxylic acid (2) as the sole product in high yield, which could be converted to olivacine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In 2004, Miki et al reported the total synthesis of olivacine ( 28.10 ) and ellipticine ( 28.9 ) starting from common precursors, N -benzylindole-2,3-dicarboxylic anhydride ( 318.1 ) and 2,4,6-trimethoxypyridine ( 318.2 ) (Scheme ). , Previously, the same group had already reported a synthesis of ellipticine ( 28.9 ) starting from the same indole precursor 318.1 . Friedel–Crafts acylation of 2,4,6-trimethoxypyridine ( 318.2 ) with N -benzylindole-2,3-dicarboxylic anhydride ( 318.1 ) in the presence of titanium(IV) chloride in dichloromethane afforded regioselectively the 3-acylindole-2-carboxylic acid 318.3 , which was transformed to ketone 318.4 by reaction with copper chromite in quinoline. , The ketone 318.4 was transformed to the monomethyl derivative 318.5 by regioselective methyl ether cleavage with 47% hydrobromic acid, treatment with triflic anhydride (Tf 2 O), and subsequent reaction of the corresponding triflate with MeMgBr in the presence of NiCl 2 (dppe) 2 (70% yield over 3 steps) . Regioselective O-demethylation of 318.5 by treatment with boron tribromide followed by reductive removal of the ketone oxygen atom with diborane and subsequent treatment with triflic anhydride (Tf 2 O) afforded the 4-pyridyl triflate 318.6 .…”
Section: Pyrido[43-b]carbazole Alkaloidsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2004, Miki et al reported the total synthesis of olivacine ( 28.10 ) and ellipticine ( 28.9 ) starting from common precursors, N -benzylindole-2,3-dicarboxylic anhydride ( 318.1 ) and 2,4,6-trimethoxypyridine ( 318.2 ) (Scheme ). , Previously, the same group had already reported a synthesis of ellipticine ( 28.9 ) starting from the same indole precursor 318.1 . Friedel–Crafts acylation of 2,4,6-trimethoxypyridine ( 318.2 ) with N -benzylindole-2,3-dicarboxylic anhydride ( 318.1 ) in the presence of titanium(IV) chloride in dichloromethane afforded regioselectively the 3-acylindole-2-carboxylic acid 318.3 , which was transformed to ketone 318.4 by reaction with copper chromite in quinoline. , The ketone 318.4 was transformed to the monomethyl derivative 318.5 by regioselective methyl ether cleavage with 47% hydrobromic acid, treatment with triflic anhydride (Tf 2 O), and subsequent reaction of the corresponding triflate with MeMgBr in the presence of NiCl 2 (dppe) 2 (70% yield over 3 steps) . Regioselective O-demethylation of 318.5 by treatment with boron tribromide followed by reductive removal of the ketone oxygen atom with diborane and subsequent treatment with triflic anhydride (Tf 2 O) afforded the 4-pyridyl triflate 318.6 .…”
Section: Pyrido[43-b]carbazole Alkaloidsmentioning
confidence: 99%
“…Debenzylation of 318.8 with 47% hydrobromic acid afforded 3-methoxyolivacine ( 318.9 ). After O-demethylation of 318.9 , the corresponding hydroxy derivative was transformed to the triflate, which on subsequent treatment with ammonium formate in the presence of Pd(PPh 3 ) 4 in hot methanol led to olivacine ( 28.10 ) …”
Section: Pyrido[43-b]carbazole Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations